Modeling the economic and environmental impacts of cattle ranching intensification in Mato Grosso - Batista, Evandro Lima da Silveira (2016)
Cattle ranching occupy more land than any other production activity in Brazil and accounts for 44% of greenhouse gas (GHG) emissions from the land use sector. In response, Brazil has proposed a large-scale pasture restoration target as a mitigation measure for its Nationally Determined Contribution (NDC). Pasture restoration is, however, only one option in a portfolio of investments that could be brought to bear to encourage intensification in beef production. To analyze the potential impacts, i.e. economic and overall GHG emissions, from mixes of intensification strategies―from pasture restoration to improved health and reproductive management, pasture supplementation, and feedlot operations―, we developed a simulation model of the cattle ranching system (SimPec) and applied it to Mato Grosso state. Our results show that large-scale pasture restoration, instead of reducing GHG emissions, threatens the success of Brazil’s NDC. Soil carbon fixation after pasture restoration does not compensate marginal emissions due to higher stock densities; simply increasing beef production will lead to an overall rise in GHG emissions from the cattle sector. Rather than pasture restoration, investments in confinement operations along with complementary improvements in production strategies are more likely to prompt better economic, productive, and, in particular, environmental outlooks for the cattle sector in Brazil.